Visualization of Integrated Student’s Attendance Data using PowerBI - Saadan, Mohammed Nor Syahmi (IRC, 2020)
University Technology of Petronas is a private universities consists of 5000- 8000 students overall. Managing the attendance system with such a big data can be troublesome. Not just for supervising the management system, making an analysis out of the attendance data can become a hardship especially when dealing with big data entry. A keen analysis must be done in order to visualize more possibilities that can be gained after analysing the data. Student productivity can be increased by having the right data visual. Analysing the data of the student’s attendance can be the best way to monitor the student’s productivity. The current system that are being implemented in UTP have a few drawbacks such as no proper data integration, difficult and limited analysis of rich data due to silo Excel sheets and last but not least, no wholesome analysis is yet been conducted. The present system that are being used to keep the data of the student attendance are in Excel spreadsheets. Then, the data are transferred and stored in SharePoint for further use. Making an analysis in Excel spreadsheets are not an easy works and only limited amount of analysis can be conducted. By using PowerBI, the analytic works can be improved to a higher classification of data. It helps in analysing the data and also visualize the student’s attendance data in graphical illusions. Also, when dealing with multiples sets of data, an integration technique needs to be perform in order to standardize a data. This project helps the lecturers and other units such as the Student Attendance Committee and ITMS in making a better analyzation of the student’s attendance data. It provides them with a platform to view the analysis made and monitor the student’s productivity. With this project, it helps UTP to have an integrated and centralized data in Excel. It also provides UTP with a dashboard that contains graphical analysis on the data of the student’s attendance.